Care‐full Justice in the City. Issue 3 (17th August 2016) - Williams, Miriam J.
Abstract: Feminist theorists in geography and beyond have long been calling for an ethic of care to be considered alongside justice as a normative ideal that can assist us in repairing our world. In urban theory this call has largely remained unheard as an ethic of care remains absent from theorisations of what comprises a just city. In this paper I argue for care to be considered alongside justice as an equally important ethic in our search for justice in the city. I develop the concept of care‐full justice, which assists us in negotiating the inherent tension between the normative and situated in the search for the ideals, and actually existing expressions, of justice and care in the city. I demonstrate the generative potential of this concept and argue that it enables us to re‐think what cities can be and to reveal times and places where this is the case.